The host status of Brassicaceae to Meloidogyne and their effects as cover and biofumigant crops on root-knot nematode populations associated with potato and tomato under South African field conditions. (August 2018) - Daneel, M.; Engelbrecht, E.; Fourie, H.; Ahuja, P.
Abstract: Cover and biofumigant crops of Brassicaceae are potential alternatives to synthetically-derived nematicides for managing root-knot nematode pests in various crops. The host status of Eruca sativa (cvs. Rocket Trio and Nemat), Brassica juncea (cvs Calienté and Fumigreen) and Raphanus sativus (cvs Doublet and Terranova) were determined for Meloidogyne incognita and Meloidogyne javanica in separate glasshouse experiments. Additionally, the efficacy of such cover- and biofumigant crops (after incorporation of their aerial parts) was evaluated against root-knot nematode populations at two field sites (potato and tomato, respectively). All cover crops evaluated in the glasshouse showed resistance against both Meloidogyne spp., except B. juncea cv. Calienté to M. incognita . None of the Brassicaceae crops used in the potato study, however, resulted in a significant reduction of population levels of M. incognita in roots and tubers of the Brassicaceae in the follow-up potato crop. In contrast, only cv. Nemat reduced Meloidogyne spp. population densities significantly in tomato roots, while cvs Doublet, Terranova and Rocket Trio reduced population densities substantially. Plant-growth parameters, viz. plant length and mass as well as yield (fruit mass and number of fruits harvested) were significantly higher for tomato grown in plots where cvs. Doublet and Rocket Trio grew and their aerial parts incorporated. Although variable, Brassicaceae cvs evaluated showed potential as an alternative management strategy against root-knot nematodes. Highlights: Host-status evaluations of E. sativa, B. juncea and R. sativus for M. incognita and M. javanica were conducted. In the potato experiment, relatively high population densities of M. incognita were found on cover crop treatments. In the tomato experiment, most Brassicaceae crops tested reduced population densities of a mixed root-knot populations. Results demonstrated that the same cultivars can react differently under different abiotic and biotic conditions.